KAJIAN ASPEK KEBIJAKAN DAN REGULASI DALAM MASALAH PENGELOLAAN LIMBAH CAIR INDUSTRI RUMAH TANGGA - Petrus Nugro Rahardjo (Jurnal Ecolab, 2009)
Water pollution due to the domestic wastewater produced by the local community and their home industries in a bigcity, such as Jakarta, has already been inviting many environmental problems since the last ten years. Based on theresearch done by Directorat General Cipta Karya, Public Works Department RI, domestic wastewater in Jakartadelivers 75% of all pollutants in surface water pollution. Therefore many things should be done to solve those waterpollution problems. A lot of environmentally related rules have established in Indonesia, but they are not able to beoptimally implemented because of some weaknesses of the environmental rule contents. One of the solving optionsis to create a perfect regulation system for wastewater management. The laws for home industry wastewater management,especially in big cities, have to be perfectly completed, mainly in the field of standard, operation and procedure,the wastewater quality standard, the adequate and qualified technology, the landscape and building planningand the institutional coordination. If the all environmental regulations are well synchronized, the law enforcementwill be simply implemented. By applying them consistently, the water pollution control can be handled well.